Membangun Kelembagaan Penyediaan Informasi Publik Desa dalam Rangka Menjamin Penuhan Hak Konstitusional Masyarakat Desa di Kabupaten Serang - Juliannes Cadith; Rina Yulianti (Jurnal Administrasi Publik, 2022)
The discussion of public information disclosure in the village in the midst of a paradigm shift from goverment to governance is very interesting indeed. This places the strategic position of the village community not only as an object of service and development but also as a subject of development in the village. Various facts show that the village has not become a major concern in the development of information disclosure. This research is a descriptive research with a qualitative approach. The required information is collected using narrative interviews, observation and literature study. Informants from the study were determined purposively using snowball sampling. In this article, the four levels of the Williamson model are used to analyze it. The results show that the development of public information institutions in the village in Serang Regency at the macro and micro levels has not supported the realization of information disclosure in the village. It can be seen at level one that various informal rules in the form of traditions, norms and habits that live in rural communities are not yet compatible in supporting the formal rules of information disclosure. At the second level, there has not been any recognition and awareness of either the public or public organizations to fulfill the public's rights regarding the disclosure of public information. At the third level, the institutional governance of public information disclosure has not been developed effectively to be able to minimize transaction costs. At the fourth level, the systematization of rules related to authority, organization, administration, human resources, finance, hierarchical relations, supervision, as well as work procedures and mechanisms need attention.